Assessment of current and future spatial suitability of market-demanded old and new common bean varieties in Tanzania - Kalemera, Sylvia Monica; Venkataramana, Pavithravani B.; Mbega, Ernest R.; Assefa, Teshale; Ijumulana, Julian; Ochieng, Justus; Rubyogo, Jean Claude (Frontiers in Agronomy, 2026)
Climate change is projected to reduce land suitable for common bean cultivation in Sub-Saharan Africa. This poses serious risks to food security and livelihoods, especially as most farmers continue to grow older varieties under changing conditions. This study evaluated current and future suitability of common bean varieties in Tanzania by comparing older (>10 years) and newly released, market-preferred cultivars under a CMIP6 climate scenario. Suitability was analyzed for near-current (1970–2000) and future (2021–2040) periods using the Targeting Tool Kit and land suitability models in R. Model outputs were validated with 98.7% accuracy. By 2040, highly suitable areas are projected to decline by 4.9%, while low-suitability areas may expand by 31.2%. Older varieties (JESCA, UYOLE 03) experience the greatest reductions (–5.7%, –5.0%), whereas newer varieties show greater resilience. TARIBEAN7 shows no clear spatial advantage over Lyamungu 90. Although JESCA may decline under future climates, its strong environmental predictability makes it a valuable reference variety for breeding. Altitude, rainfall, and soil properties remain dominant factors shaping suitability. Findings highlight the need for climate-smart and area -targeted breeding, broader seed dissemination, and improved soil management to sustain production and resilience.